Immunodeficiency in a case diagnosed with Smith-Magenis syndrome - Kılınçkaya, Lütfi; Özdemir, Öner (Alergologia Polska - Polish Journal of Allergology, 2026)
Smith-Magenis syndrome is a complex genetic disorder caused by deletion or mutation of the retinoic acid-induced 1 gene located primarily on chromosome 17p11.2. This syndrome is characterized by a series of physical, developmental, and behavioral abnormalities, including immune deficiencies presenting as recurrent infections. We report a 4-year-old male patient who presented to the pediatric immunology-allergy clinic with the complaint of frequent illnesses with the diagnosis of Smith-Magenis syndrome. As a result of the clinical and laboratory examinations, the patient was diagnosed with IgG subclass deficiency and was started on intravenous immunoglobulin replacement therapy. Recurrent infections associated with antibody deficiencies represent a very rare critical aspect of the syndrome that requires further investigation in the clinical setting. The complexity of Smith-Magenis syndrome necessitates an integrated healthcare strategy to provide holistic management of this multifaceted condition and highlights the need for ongoing research into its genetic, immunological, and neurodevelopmental dimensions. This rare case report sheds light on further research and provides a better understanding of the clinical presentation of the syndrome.